Intravenous iron or placebo for anaemia in intensive care: the IRONMAN multicentre randomized blinded trial: A randomized trial of IV iron in critical illness - The, I.; Litton, E.; Baker, S.; Erber, W.; Farmer, Shannon; Ferrier, J.; French, C.; Gummer, J.; Hawkins, D.; Higgins, A.; Hofmann, Axel; De Keulenaer, B.; et al. (Springer-Verlag, 2016)
Purpose: Both anaemia and allogenic red blood cell transfusion are common and potentially harmful in patients admitted to the intensive care unit. Whilst intravenous iron may decrease anaemia and RBC transfusion requirement, the safety and efficacy of administering iron intravenously to critically ill patients is uncertain. Methods: The multicentre, randomized, placebo-controlled, blinded Intravenous Iron or Placebo for Anaemia in Intensive Care (IRONMAN) study was designed to test the hypothesis that, in anaemic critically ill patients admitted to the intensive care unit, early administration of intravenous iron, compared with placebo, reduces allogeneic red blood cell transfusion during hospital stay and increases the haemoglobin level at the time of hospital discharge. Results: Of 140 patients enrolled, 70 were assigned to intravenous iron and 70 to placebo. The iron group received 97 red blood cell units versus 136 red blood cell units in the placebo group, yielding an incidence rate ratio of 0.71 [95 % confidence interval (0.43–1.18), P = 0.19]. Overall, median haemoglobin at hospital discharge was significantly higher in the intravenous iron group than in the placebo group [107 (interquartile ratio IQR 97–115) vs. 100 g/L (IQR 89–111), P = 0.02]. There was no significant difference between the groups in any safety outcome. Conclusions: In patients admitted to the intensive care unit who were anaemic, intravenous iron, compared with placebo, did not result in a significant lowering of red blood cell transfusion requirement during hospital stay. Patients who received intravenous iron had a significantly higher haemoglobin concentration at hospital discharge. The trial was registered at http://www.anzctr.org.au as # ACTRN12612001249842.